INMUNOLOCALIZACIÓN Y CONTENIDO DE ESTEROIDES SEXUALES EN OVARIOS DE HEMBRAS DE PEROMYSCUS MELANOTIS ALLEN & CHAPMAN, 1897 (RODENTIA: MURIDAE) DURANTE LA PRIMERA MITAD DE LA PREÑEZ - Salame Méndez, Arturo; Vigueras Villa Señor, Rosa María; Herrera Muñoz, Joaquín; Mendieta Márquez, Enrique; Salgado-Ugarte, Isaías H.; Castro-Campillo, Alondra; Ramírez Pulido, José (Instituto de Ecología, A.C., 2003)
Ovarian histology, sexual steroids contents and their localization within the gonads were analyzed in females of Peromyscus melanotis during the first half of their pregnancy. The ovaries showed follicules in different growth stages and fully secreting corpora lutea. Ovarian concentrations of pregnenolone (P5), progesterone (P4), 17-hydroxy-progesterone (17P4), androstenedione (A ), testosterone (T), and estradiol (E2) were analyzed by radioimmunoassay (RIA ). P4 was the steroid with the highest concentrations, followed by P5, T, E2, 17P4, and A , respectively. Inmunohistochemical analyses revealed that P4 is mainly located in the corpora lutea and that E2 can be found both in the Salame-Méndez et al.: Contenido de esteroides en hembras de Peromyscus melanotis estroma and in the follicular cells. Our results suggest that during the first half of the pregnancy, folliculogenesis is maintained in P. melanotis, and that the corpus luteum constitutes the main, although not the only, steroidogenic tissue within the ovary.